The effect of incentives, work motivation and job satisfaction on the employee performance of the Air Hangat Barat District office at Kerinci Regency - Suhelmi Helia; Bibendri Bibendri; Jerry Supriawan; Asrina Yanti (Institute of Computer Science (IOCS), 2023)
This study aims to see the effect of (1) Incentives on the performance of employees of the Air Hangat Barat district Office, Kerinci Regency (2) Work motivation on the performance of employees of the Air Hangat Barat District Office, Kerinci Regency (3) Job satisfaction on the performance of employees of the Air Hangat Barat District Office ,Kerinci Regency (4) Incentives, work motivation and job satisfaction together affect the performance of employees of the Air Hangat Barat District Office. The sampling method used for this study was total sampling with a sample of 30 people. Data analysis was carried out using SPSS (Statistical Program for Social Science). The results of this study show that (1) Incentives have a significant positive influence on the performance of employees of the Air Hangat Barat District Office, Kerinci Regency (2) Work motivation has a positive influence on the performance of employees of the Air Hangat Barat District Office, Kerinci Regency (3) Job satisfaction have a positive influence on the performance of employees of the Air Hangat Barat District Office of Kerinci Regency (4) Incentives, work motivation and job satisfaction together have a positive effect on the performance of employees of the Air Hangat Barat District Office of Kerinci Regency.